Anti‐SARS‐CoV‐2 Inhibitory Profile of New Quinoline Compounds in Cell Culture‐Based Infection Models. Issue 4 (18th January 2022) - Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Marschall, Manfred; Tsogoeva, Svetlana B.
Abstract: Invited for the cover of this issue are Manfred Marschall, Svetlana B. Tsogoeva and co‐workers at Friedrich‐Alexander University of Erlangen–Nürnberg. The image depicts a new anti‐SARS‐CoV‐2 compound in front of SARS‐CoV‐2 viruses. Read the full text of the article at 10.1002/chem.202103861 . Abstract : " A fruitful collaboration on the development of highly potent hybrid compounds with anti‐cytomegalovirus activity ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202103861 ).